Tracking the development of agrammatic aphasia: A tensor-based morphometry study. (May 2017) - Whitwell, Jennifer L.; Duffy, Joseph R.; Machulda, Mary M.; Clark, Heather M.; Strand, Edythe A.; Senjem, Matthew L.; Gunter, Jeffrey L.; Spychalla, Anthony J.; Petersen, Ronald C.; Jack, Clifford R.; Josephs, Keith A.
Abstract: Agrammatic aphasia can be observed in neurodegenerative disorders and has been traditionally linked with damage to Broca's area, although there have been disagreements concerning whether damage to Broca's area is necessary or sufficient for the development of agrammatism. We aimed to investigate the neuroanatomical correlates of the emergence of agrammatic aphasia utilizing a unique cohort of patients with primary progressive apraxia of speech (PPAOS) that did not have agrammatism at baseline but developed agrammatic aphasia over time. Twenty PPAOS patients were recruited and underwent detailed speech/language assessments and 3T MRI at two visits, approximately two years apart. None of the patients showed evidence of agrammatism in writing or speech at baseline. Eight patients developed aphasia at follow-up (progressors) and 12 did not (non-progressors). Tensor-based morphometry utilizing symmetric normalization (SyN) was used to assess patterns of grey matter atrophy and voxel-based morphometry was used to assess patterns of grey matter loss at baseline. The progressors were younger at onset and more likely to show distorted sound substitutions or additions compared to non-progressors. Both groups showed change over time in premotor and motor cortices, posterior frontal lobe, basal ganglia, thalamus and midbrain, but the progressors showed greater rates of atrophy in left pars triangularis, thalamus and putamen compared to non-progressors. The progressors also showed greater grey matter loss in pars triangularis and putamen at baseline. This cohort provided a unique opportunity to assess the anatomical changes that accompany the development of agrammatic aphasia. The results suggest that damage to a network of regions including Broca's area, thalamus and basal ganglia are responsible for the development of agrammatic aphasia in PPAOS. Clinical and neuroimaging abnormalities were also present before the onset of agrammatism that could help improve prognosis in these subjects.